Gamma-ray method of radial-clearance determination for engine crankshafts; Soviet Journal of Nondestructive Testing; Vol. 12, iss. 6 - Boiko D. A.; Burov G. I.; Chakhlov V. L. Vladimir Lukianovich; Shtein M. M. Mikhail Mikhailovich (1976, 1976)
A radiation method is described for determining clearances in crankshaft bearings without dismantling; the method involves measuring the positions of the piston at top dead center, which are affected by the inertial and compression forces during running. The block diagram is presented, together with the method of measuring the clearance and test data for a YaMZ-238 internal combustion engine.